Operations management strategies for the textile-clothing sector in Colombia (2019)
The textile and clothing industry in Colombia is facing several challenges that have motivated the redesign and optimization of production and logistics processes to remain competitive in global markets. The purpose of this paper is to introduce operations management strategies to create value and address the intense competition in both the national and international markets for the textile-clothing sector in Colombia. Strategies focused on inventory management, over inventory and overproduction, and reducing high production costs are proposed. It is concluded that operations management allows addressing current problems for the textile-clothing sector through integrating, optimizing and coordinating business processes for the long, medium and short term. © 2019 International Business Information Management Association (IBIMA).